Influence of electronic and molecular structure on the fragmentation dynamic of even-electron carbocationic triangulenes and helicenes in the gas phase - Hitzenberger, Jakob; Uhl, Agnes; Schatz, Jürgen; Drewello, Thomas (Journal of Mass Spectrometry, 2017)
Stable, long-lived organic cations are directly transferred by electrospray ionization (ESI) from solution into the gas phase where their collision-induced dissociations (CID) are studied by tandem mass spectrometry. Three related types of triphenyl carbenium ions are investigated, in which the meta positions are either substituted by methoxy groups or tertiary nitrogen bridges, including tetramethoxyphenylacridinium (TMPA+), dimethoxyquinacridinium (DMQA+), and triazatriangulenium (TATA+) cations. These ions are triangular in shape with increasing degrees of planarity. Fragmentation occurs at the periphery of the triangular molecule, involving the methoxy groups and the substituent of the nitrogen bridge. Each initial precursor cation is an even electron (EE) system and shows competing dissociations into both even (EE) and odd electron (OE) fragment ions. The latter reaction is a breach of the classic ‘even-electron rule’ in mass spectrometry. While the EE fragment dissociates similar to the precursor, the OE fragment ion shows a rich radical-induced fragmentation pattern. Two driving forces direct the fragmentation of the EE precursor ion toward OE fragment ions, including the release of stabilized radicals and the extension of the π-system by increasing planarization of the triangulene core.
Keywords: Triangulenium salt; mass spectrometry